Analysis of the Impact of the Family Hope Program (PKH) Policy in the Era of the Covid-19 Pandemic - Sri Endang Rahayu; Ade Fitriani Harahap (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study aims to analyze the impact of the Family Hope Program policy in the era of the covid-19 pandemic in Ulumahuam Selatan Village, Silangkitang District, Labuhanbatu Regency, North Sumatra Province. The basic method used in this research is to use descriptive analysis approach. The research location was conducted in Ulumahuam Village, Silangkitang District, South Labuhanbatu Regency. The total population in the study amounted to 359 residents. This study determined 50 respondents using purposive sampling. The data analysis technique used is descriptive analysis. The results of the study show that the quality of life of households receiving PKH policies during the COVID-19 pandemic, their quality of life decreased compared to before the pandemic. This is because the people receiving PKH are increasingly difficult, this is shown from the respondents' answers to the average monthly data income of respondents. answered Rp. 500,000 to Rp. 1,000,000 million because during the covid 19 pandemic their business was quiet and some of their business was closed. There are differences between the PKH policies before the Pandemic and the PKH policies during the Pandemic, it can be seen that the amount of funds received before the pandemic for pregnant women was IDR 2,400,000 while during the pandemic it changed to IDR 3,000,000. Likewise, funds for early childhood, elementary, junior high, high school, severe disabilities and the elderly. Not only that, assistance in the form of basic necessities has also changed or the government has increased the amount of basic food assistance which was previously Rp. 150,000/Family, to Rp.200,000/Family. With the PKH policy, it is hoped that the poor will decrease, but in fact the poor are increasing in Labuhan Batu Selatan Regency.